Capillary Blood Glucose measurement in clinical Dental: tracking cases of Type II Diabetes - Ramos, Ruth Tramontani (2014)
Estimates show that in 2025, the Brazilian population is expected to reach 228 million. The type 2 Diabetes was the third leading cause of death in Brazil (Censo 2010). By 2025, should be about 11 million diabetics in the country, representing an increase of over 100 % compared to 5 million in 2000. This study aims to track possible cases through benchmarking test postprandial blood glucose. The evaluation of 69 women and 34 men showed a percentage of 8% possible cases which had mean postprandial blood glucose of more than two hours of 232.75 mg/dl and a maximum of 412mg/dl in agreement with Ministry of Health studies.